Effect of fuels on conductivity, dielectric and humidity sensing properties of ZrO2 nanocrystals prepared by low temperature solution combustion method*. Issue 3 (1st September 2016) - Madhusudhana, H.C.; Shobhadevi, S.N.; Nagabhushana, B.M.; Chaluvaraju, B.V.; Murugendrappa, M.V.; Hari Krishna, R.; Nagabhushana, H.; Radeep, N.R.
Abstract: ZrO2 nanopowders were synthesized by low temperature solution combustion method using two different fuels namely glycine and oxalyldihydrazide (ODH). The phase confirmation was done by powder X-ray diffraction (PXRD) and Raman spectral analysis. Use of glycine resulted in ZrO2 with mixture of tetragonal and monoclinic phase with average crystallite size of ∼30 nm. However, ODH as fuel aids in the formation of ZrO2 with mixture of tetragonal and cubic phase with average crystallite size ∼20 nm. Further, in present work we present novel way to tune conductivity property of the nano ZrO2 . We show that merely changing the fuel from glycine to ODH, we obtain better DC conductivity and dielectric constant. On the other hand use of glycine leads to the formation of ZrO2 with better AC conductivity and humidity sensing behavior. The dielectric constants calculated for samples prepared with glycine and ODH were found to be 45 and 26 respectively at 10 MHz. The AC and DC conductivity values of the samples prepared with glycine was found to be 9.5 × 10 −4 S cm −1, 1.1 × 10 −3 S cm −1 and that of ODH was 7.6 × 10 −4 S cm −1, 3.6 × 10 −3 S cm −1 respectively.